May allergy have a role in primary or recurrent otitis media in Egyptian pediatric patients: a prospective study. Issue 1 (1st January 2021) - El-Shahat, Mohammed; ElSharkawy, Asser; Shahin, Doaa; Barakat, Ghada; Moneir, Waleed
ABSTRACT: This study aimed to estimate the levels of total serum IgE and assess the presence of eosinophils in middle ear fluid in primary and recurrent otitis media with effusion in Egyptian pediatric patients. A prospective study of 59 children with bilateral otititis media effusion (OME) were enrolled in this study. All patients had refractory OME to non-surgical lines of treatment. Full history was taken then detailed ENT examination followed by various investigations in the form of pure tone audiometry, tympanometry, serum total IgE, and eosinophilia. The incidence of allergic dermatitis, food allergy, allergic conjunctivitis, and anaphylaxis were (64.4%), (32.2%), (33.9%), (10.2%), (8.5%), and (5.1%), respectively. In this study middle ear effusion, eosinophils were positive in (61%). Total IgE was high in 40 children (67.8%). There was a strong relationship of recurrent OME with allergic manifestations, serum IgE, middle ear effusion fluid eosinophils, and blood eosinophilia suggesting intimately important role of allergy in the recurrence of OME. Allergy has a fundamental role in the pathogenesis of recurrent OME. The possibility of allergy should be considered in OME cases that did not improve with conventional lines of treatment.